Pengembangan Rekayasa Perangkat Lunak Online Sistem E-Recruitment pengawai PT.FM Global Logistics Berbasisi web - Indah Yani Daeli; Aryanto Nur (CV. ITTC INDONESIA, 2024)
The E-Recruitment System for Employees of PT. FM Global Logistics Web-Based under the guidance of Ir. Ifan Junaedi, S.Kom A Web-Based Employee Admission Information System or e-recruitment can be used as a solution in handling the employee recruitment process in a company. With the existence of a web-based employee admission information system or e-recruitment, companies can choose the right employees for the company, besides that companies can process applicant data in a database so that applicant data does not accumulate in the filing cabinet. In this study, the author discusses how to design a web-based employee admission information system or e-recruitment at PT. FM Global Logistics. The system development methodology used is the System Development Life Cycle (SDLC) Waterfall model with tools using Unified Modeling Language (UML) on the system which includes the stages of system planning, system analysis, system design and system implementation